Social Realities in Ahmad Tohari’s Di Kaki Bukit Cibalak: An Alan Swingewood Sociological Literary Analysis - Herson Kadir; Eva Putri Magfirah; Novita Abas; Anesa Dwinarti Tute; Jein Latif; Marwah Ali; Yunitasari A. Umar (Universitas Islam Negeri Palopo, 2026)
This study aims to reveal the social reality of society depicted in Ahmad Tohari’s novel DKBC (Di Kaki Bukit Cibalak) using the literary sociology perspective according to Alan Swingewood. Alan Swingewood’s concept views literary works as socio-cultural documents, where literature is related to the author’s life background and historical aspects. The research focuses on aspects of poverty, social injustice, and abuse of power depicted in the novel. The research method employed in this study is a descriptive-analytical approach using literary sociology. The primary data source is the tenth revised edition of the novel DKBC, published in 2026 by Gramedia Pustaka Utama. The research data consists of quotations related to the social realities of the community. Data collection was conducted using the read and record. Data analysis was conducted through the data reduction stage; reading, classifying, and presenting data; describing, analyzing, and interpreting; and the verification stage: drawing conclusions from the research data. The research results show that in the novel DKBC, the issue of poverty is depicted through limited access to basic necessities, inadequate housing, and the difficulty of the community in finding employment, as well as low incomes. Aspects of social injustice are evident in discriminatory treatment by village officials, social exclusion of residents involved in corruption, and the imbalance of rights between the underprivileged and those in power. As for the aspect of abuse of power, this is demonstrated through the actions of village officials and cooperative administrators who exploit their positions for personal and group gain. Based on these research findings, it can be concluded that the novel DKBC functions not only as a work of fiction but, from a historical perspective, also as a reflection of the social life of rural Indonesian communities in the 1970s.